A 2.4GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation and preparation method thereof
By adding Al elements to high-cobalt nickel secondary hardened steel to form NiAl phase and M2C re-phase precipitation, the problem of strength improvement and plastic toughness maintenance is solved, and tensile strength up to 2400MPa and excellent plastic properties are achieved, which broadens the return Thermal treatment window is suitable for aerospace applications.
Patent Information
- Application Number
- CN202310476749.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-04-28
AI Technical Summary
The existing high-cobalt nickel secondary hardened steels such as M54 steel have not yet reached more than 2000MPa, and the problem of maintaining plastic toughness while improving the strength, especially when adding new elements to complex alloy systems, faces the contradiction between nano-scale precipitation phases and Risk of loss of plastic toughness.
By adding 1% Al element to the M54 steel, nanoscale NiAl intermetallic compounds are introduced to make them precipitate with the original M2C carbides, thereby achieving the improvement of high yield strength and tensile strength, and through regulation The heat treatment conditions ensure the stability and plasticity of the precipitated phase.
The strength of high-cobalt nickel secondary hardened steel has been significantly improved, reaching tensile strength above 2400MPa, while maintaining good plasticity, widening the tempering heat treatment window, ensuring the stability and elongation of the precipitation phase, solving the single Problems of sensitive precipitation phase outage.
Smart Images

Figure BDA0004205760740000011 
Figure HDA0004205760750000011 
Figure HDA0004205760750000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy steels, and in particular relates to a 2.4 GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation and a preparation method thereof. Background Art
[0002] Aircraft applications, especially landing gear, require steel with high mechanical resistance, fracture toughness and resistance to stress corrosion cracking. For decades, 300M steel has been widely used in aircraft landing gear, but its fracture toughness and resistance to stress corrosion cracking need to be improved.
[0003] High cobalt-nickel secondary hardening steel was developed in the late 1960s to optimize 300M steel. The main idea is to replace cementite with M2C alloy carbide precipitation during tempering to avoid brittle fracture and achieve a significant increase in fracture toughness. After nearly half a century of development, its application has become more and more extensive by continuously improving strength and optimizing strength-toughness balance. Representative ones include AF1410, AerMet100, M54, etc., and their chemical compositions are shown in Table 1.
[0004] Table 1 Chemical composition of typical high cobalt-nickel secondary hardening steel (wt.%)
[0005] Steel Type C Ni Co Cr Mo W V AF1410 0.16 10.0 14.0 2.0 1.0 - - AerMet100 0.23 11.0 13.4 3.1 1.2 - - M54 0.30 10.0 7.0 1.0 2.0 1.3 0.1
[0006] Table 2 Room temperature mechanical properties of typical high cobalt-nickel secondary hardening steels
[0007]
[0008] At present, as the latest generation of high-cobalt-nickel secondary hardening steel, M54 steel has excellent comprehensive performance, but its maximum strength is still far from the actual demand. The main source of strength of M54 steel is the precipitation strengthening caused by the precipitation of nano-scale needle-shaped M2C carbides precipitated in the martensite matrix during tempering. 516℃10h is its peak aging process. If you want to further improve the strength and make the strength of high-cobalt-nickel secondary hardening steel exceed 2000MPa, the current composition should be difficult to achieve. The most effective and feasible method is to introduce another nano-scale precipitation phase by designing the composition. High-cobalt-nickel secondary hardening steel has a high alloy element content and a relatively complex system. Whether other elements can be successfully precipitated after adding them, and whether they will not contradict the precipitation of M2C, and whether they will cause huge losses in plasticity and toughness, are also problems often encountered when introducing new precipitation. So, under the premise of ensuring the most basic plasticity and toughness requirements, how to further improve the strength of M54 steel is the focus issue to be solved. Summary of the invention
[0009] The object of the present invention is to provide a high-cobalt-nickel secondary hardening ultra-high strength steel that realizes M2C and NiAl complex phase precipitation, has good comprehensive performance, has a tensile strength of more than 2.4 GPa and good plasticity.
[0010] This high-performance secondary hardening ultra-high strength steel, based on M54 steel, adopts the design concept of regulating the precipitation phase to improve precipitation strengthening, adds Al elements to introduce NiAl intermetallic compounds, and makes nano-scale M2C and NiAl phases precipitate in combination to obtain high strength. To achieve the above goals, on the basis of the current high-cobalt-nickel secondary hardening steel M54 alloy composition, 1% Al elements are added to introduce nano-scale NiAl phases that can bring significant precipitation strengthening effects, realize complex phase precipitation with M2C carbides, and achieve high yield strength and tensile strength in the form of composite precipitation strengthening.
[0011] The technical solution of the present invention is:
[0012] A 2.4GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation has the following chemical composition weight percentages: C 0.2-0.4%, Ni 9.5-10.5%, Co 6.5-7.5%, Cr 0.6-1.2%, Mo 1.8-2.2%, W 1.0-1.5%, Al 0.8%-1.2%, V 0.1-0.3%, and the balance is Fe and unavoidable impurities.
[0013] A method for preparing the above-mentioned 2.4 GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation, comprising the following steps:
[0014] Step 1: preparing an alloy ingot of the above composition by using a vacuum induction furnace, smelting and casting the alloy ingot into a steel ingot, and then smelting and forging the steel ingot;
[0015] Step 2: Normalizing and annealing heat treatment;
[0016] Step 3: Solution treatment: heat to 1045-1075°C, keep warm for 1-1.5 hours after heating through, oil quench; then perform deep cryogenic treatment in liquid nitrogen, keep warm at -73°C for 1-3 hours and then warm to room temperature in air;
[0017] Step 4: Tempering treatment: Heat to 460-540℃, keep warm for 8-12 hours after heating through, and air cool.
[0018] Furthermore, the smelting conditions in step 1 are: after smelting and casting into a steel ingot using a vacuum induction + vacuum consumable remelting or vacuum induction + electroslag remelting smelting process, the steel ingot is homogenized at 1100-1300° C. and the insulation time is 3-10 hours.
[0019] Furthermore, the forging conditions in step 1 are: 1040-1060° C., and heat preservation for 1 hour.
[0020] Furthermore, the normalizing treatment conditions in step 2 are 1060-1088° C. and kept warm for 1-2 hours.
[0021] Furthermore, the annealing process described in step 2 is: first subcritical annealing: 785-813° C., keeping warm for 1-2 hours; air cooling, and then annealing: 624-680° C., keeping warm for ≥8 hours.
[0022] Preferably, the step 4 may also be subjected to secondary tempering treatment, under the condition of heating to 300° C. to 400° C. and keeping the temperature for 8 to 12 hours.
[0023] The advantages of the present invention are:
[0024] (1) By adding 1% Al element to the high cobalt-nickel secondary hardening steel M54 steel, a nano-scale intermetallic compound NiAl with severe precipitation strengthening is formed with the high content of Ni element in the high cobalt-nickel secondary hardening steel. Under this system, the peak aging temperature is 480°C, and the original M2C carbide in the high cobalt-nickel secondary hardening steel M54 steel can be precipitated in a complex phase within the temperature range of 460-540°C. The two will not affect each other in terms of composition or precipitation behavior, and ultimately significantly improve the strength of the high cobalt-nickel secondary hardening steel. The shape of the intermetallic compound has little effect on the good plasticity and toughness of the high cobalt-nickel secondary hardening steel; a low-cost solution is used to achieve a strength increase of up to 400MPa;
[0025] (2) Without changing the original heat treatment method, the tempering heat treatment window is broadened. The first tempering can be arbitrarily selected within the temperature range. The peak aging of the two precipitates is within this temperature range. Higher or lower temperatures will seriously weaken the precipitation strengthening effect. The final strength can reach the requirement of 2400MPa. The second tempering is to meet the requirement of better elongation. Although this temperature range will not coarsen the precipitate phase, it will make the strengthening effect of the precipitate phase more stable. The strength is slightly lower than that after a single tempering, but the elongation is better, and the strength-plasticity match is better. To a certain extent, the problem of a single precipitate being sensitive to over-aging is solved.
[0026] (3) The room temperature performance indicators of the Al-containing high Co-Ni secondary hardening steel designed by the present invention are as follows: Yield strength σ s 2000~2200MPa, tensile strength σ b It is 2400-2600MPa, and the elongation after break δ is 5-10%. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 TEM image of the organization of Comparative Example 1;
[0028] Figure 2 TEM image of the tissue of Example 1;
[0029] Figure 3 This is the TEM image of the tissue in Example 3. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with the embodiments and comparative examples of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0031] Comparative Example 1
[0032] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0033] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0034] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0035] (4) Quenching, deep cooling and tempering heat treatment: quenching at 1060℃×1.5h, oil quenching, followed by deep cooling in liquid nitrogen at -73℃×1h, warming to room temperature in air, tempering at 520℃×10h, and air cooling. The specimen blank was ground into a mechanical property specimen.
[0036] The microstructure of the comparative example is full martensite. Figure 1 As shown, there are diffusely distributed needle-shaped M2C precipitations inside the martensite matrix, with an average equivalent radius of 3.69nm. Its mechanical properties include yield strength of 1731MPa, tensile strength of 2020MPa, and elongation of 12.1%.
[0037] Example 1
[0038] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, Al: 1.0%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0039] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0040] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0041] (4) Quenching, deep cooling and tempering heat treatment: quenching at 1060℃×1.5h, oil quenching, followed by deep cooling in liquid nitrogen at -73℃×1h, warming to room temperature in air, tempering at 520℃×10h, and air cooling. The specimen blank was ground into a mechanical property specimen.
[0042] The heat treatment method of this embodiment is exactly the same as that of comparative example 1, and the microstructure is also a full martensite structure. Figure 2 As shown in the figure, in addition to the dispersed needle-shaped M2C precipitation inside the martensite matrix, there are more nearly circular NiAl phase precipitations, and the average size of the two precipitation phases is less than 5nm. Its mechanical properties: Compared with the comparative example, the yield strength is increased from 1731MPa to 2238MPa, the tensile strength is increased from 2020MPa to 2450MPa, and the elongation is 5.1%.
[0043] Example 2
[0044] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, Al: 1.0%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0045] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0046] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0047] (4) Quenching, deep cooling and tempering heat treatment: quenching at 1060℃×1.5h, oil quenching, followed by deep cooling in liquid nitrogen at -73℃×1h, warming to room temperature in air, tempering at 480℃×12h, and air cooling. The specimen blank was ground into a mechanical property specimen.
[0048] Compared with Example 1, this embodiment has changed the tempering temperature and holding time, which is closer to the peak aging of the NiAl phase. The microstructure is the same as the above, all of which are full martensite structures. There are still two nano-scale precipitation phases inside, needle-shaped M2C and nearly circular NiAl. Its mechanical properties: compared with the comparative example, the yield strength is increased from 1731MPa to 2328MPa, the tensile strength is increased from 2020MPa to 2540MPa, and the elongation is 5.0%.
[0049] Example 3
[0050] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, Al: 1.0%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0051] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0052] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0053] (4) Quenching, deep cooling and tempering heat treatment: quenching treatment at 1060℃×1.5h, oil quenching, followed by deep cooling treatment at -73℃×1h in liquid nitrogen, warming to room temperature in air, first tempering treatment at 520℃×10h, air cooling, followed by second tempering treatment at 400℃×10h, air cooling. The specimen blank was ground into a mechanical property specimen.
[0054] Compared with the above two embodiments, this embodiment adds a second tempering, and the selected 400°C does not affect the microstructure. Figure 3The precipitates shown in the example 1 are almost unchanged, and the secondary tempering does not coarsen the two precipitates, and the size is still below 5nm. Its mechanical properties: compared with the comparative example, the yield strength is increased from 1731MPa to 2188MPa, the tensile strength is increased from 2020MPa to 2432MPa, and the elongation is 7.5%.
[0055] Example 4
[0056] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, Al: 1.0%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0057] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0058] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0059] (4) Quenching, deep cooling and tempering heat treatment: quenching treatment at 1060℃×1.5h, oil quenching, followed by deep cooling treatment at -73℃×1h in liquid nitrogen, warming to room temperature in air, first tempering treatment at 520℃×10h, air cooling, followed by second tempering treatment at 300℃×10h, air cooling. The specimen blank was ground into a mechanical property specimen.
[0060] Compared with Example 3, this embodiment adjusts the temperature of the second tempering and provides a wider second tempering temperature range, proving that the second tempering at 300°C to 400°C can form this structure and meet the mechanical property requirements. Its microstructure is also full martensite, and there are also dispersed nano-scale M2C precipitation and NiAl phase precipitation inside. Its mechanical properties: compared with the comparative example, the yield strength is increased from 1731MPa to 2143MPa, the tensile strength is increased from 2020MPa to 2406MPa, and the elongation is 8.0%.
[0061] Example 5
[0062] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, Al: 0.80%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0063] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0064] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0065] (4) Quenching, deep cooling and tempering heat treatment: quenching treatment at 1060℃×1.5h, oil quenching, followed by deep cooling treatment at -73℃×1h in liquid nitrogen, warming to room temperature in air, first tempering treatment at 520℃×10h, air cooling. The specimen blank was ground into a mechanical property specimen.
[0066] Compared with Example 1, the composition of this embodiment is different in that the Al content is changed to 0.8%, and the heat treatment method is exactly the same as that of the comparative example and Example 1. Its microstructure is a full martensitic structure, and there are also dispersed needle-shaped M2C precipitations and round NiAl phase precipitations inside the martensitic matrix, and the average size of the two precipitation phases is less than 5nm. Its mechanical properties: Compared with the comparative example, the yield strength is increased from 1731MPa to 2178MPa, the tensile strength is increased from 2020MPa to 2414MPa, and the elongation is 6.7%.
[0067] Example 6
[0068] (1) The composition of the steel is as follows: C: 0.30%, Ni: 10.00%, Co: 7.00%, Cr: 1.00%, Mo: 2.00%, W: 1.30%, Al: 1.20%, V: 0.30%, B: 0.01%, and the rest is Fe;
[0069] (2) Smelting and forging: A 25 kg vacuum induction furnace was used to prepare 21 kg of alloy ingots of the above composition. After smelting and casting into steel ingots, a high temperature homogenization treatment was first performed before forging: after keeping at 1200°C for 10 hours, the temperature was lowered for forging, and the forging heating temperature was 1050°C. The size of the forging test bar was: 50 mm × 50 mm × L;
[0070] (3) Normalizing and annealing heat treatment: normalizing at 1074°C for 1.5 h, air cooling and subcritical annealing at 810°C for 1.5 h, air cooling and annealing at 670°C for 9 h;
[0071] (4) Quenching, deep cooling and tempering heat treatment: quenching treatment at 1060℃×1.5h, oil quenching, followed by deep cooling treatment at -73℃×1h in liquid nitrogen, warming to room temperature in air, first tempering treatment at 520℃×10h, air cooling. The specimen blank was ground into a mechanical property specimen.
[0072] This embodiment adjusts the content of Al element to 1.2% as in Example 5, and the heat treatment method is the same. Its microstructure is a full martensitic structure, and there are also dispersed needle-shaped M2C precipitation and round NiAl phase precipitation inside the martensitic matrix, and the average size of the two precipitation phases is below 5nm. Its mechanical properties: compared with the comparative example, the yield strength is increased from 1731MPa to 2289MPa, the tensile strength is increased from 2020MPa to 2512MPa, and the elongation is 5.3%. Example 5 and Example 6 show that in the case of certain errors in actual production, the aluminum content of 0.8% to 1.2% can meet the mechanical property requirements.
[0073] The above embodiments can all achieve the designed strength grade requirement of 2.4GPa or above for the Al-added high-cobalt-nickel secondary hardening steel. From the perspective of microstructure, it can be seen that this high strength comes from the nano-scale NiAl precipitate phase introduced by the addition of 1% Al element, which is precipitated together with the secondary hardening phase M2C of the high-cobalt-nickel secondary hardening steel. The relatively low-cost element addition brings about a strength improvement effect of 400 to 500MPa while retaining a good elongation. In addition, the possibility of secondary tempering is provided, and a lower secondary tempering temperature that does not coarsen the precipitate phase is selected, so that the plasticity of the 2.4GPa steel is even better. Compared with the high-cobalt-nickel secondary hardening steel that requires a higher tempering temperature accuracy, the two precipitate phases broaden the tempering temperature window and are more suitable for actual production conditions. The invention can meet the strength requirements of more than 2GPa in aerospace applications and has a high application value.
Claims
1. A method for preparing a 2.4 GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation, wherein the chemical composition weight percentage of the hardened steel is: C 0.2-0.4%, Ni 9.5-10.5%, Co 6.5-7.5%, Cr 0.6-1.2%, Mo 1.8-2.2%, W 1.0-1.5%, Al 0.8%-1.2%, V 0.1-0.3%, and the balance is Fe and unavoidable impurities; It is characterized in that Here are the steps: Step 1: preparing an alloy ingot of the above composition by using a vacuum induction furnace, smelting and casting the alloy ingot into a steel ingot, and then smelting and forging the steel ingot; Step 2: Normalizing and annealing heat treatment; Step 3: Solution treatment: heat to 1045~1075℃, keep warm for 1~1.5 hours after heating through, oil quench; then perform deep cryogenic treatment in liquid nitrogen, keep warm at -73℃ for 1~3 hours and then warm to room temperature in air; Step 4: Tempering treatment: heat to 460~540℃, keep warm for 8~12 hours after heating through, and air cool. The annealing process described in step 2 is: first subcritical annealing: 785~813℃, keep warm for 1~2 hours; air cooling, then annealing: 624~680℃, keep warm for ≥8 hours; The step 4 may also be subjected to secondary tempering treatment, the conditions being heating to 300° C. to 400° C. and keeping the temperature for 8 to 12 hours.
2. The method for preparing a 2.4 GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation according to claim 1, characterized in that: The smelting conditions described in step 1 are: after smelting and casting into a steel ingot using a vacuum induction + vacuum consumable remelting or vacuum induction + electroslag remelting smelting process, the steel ingot is homogenized at 1100~1300℃ and the insulation time is 3~10 hours.
3. The method for preparing a 2.4 GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation according to claim 1, characterized in that: The forging conditions in step 1 are: 1040-1060° C., and heat preservation for 1 hour.
4. The method for preparing a 2.4 GPa aluminum-containing high-cobalt-nickel secondary hardening steel with complex phase precipitation according to claim 1, characterized in that: The normalizing treatment conditions in step 2 are 1060-1088°C and kept warm for 1-2 hours.
